Social and Cultural Impact during an Emerging Infectious Covid-19 Outbreak: A Review Study - Andi Sri Hastuti Handayani; Rian Adi Pamungkas; Andi Mayasari Usman (Alta Dharma Publisher, 2021)
A novel coronavirus (Covid-19) was a global pandemic worldwide. This review aimed to explore and describe the Covid-19 outbreak's impact on socio and culture during a pandemic situation. Electronic databases from different sources were included to extract the relevant articles. Initially, terms to retrieve related studies were “social impact,